“Chilean designers should take more advantage of copper”: Interview with Marva Griffin - Ruiz, Myriam (Base Diseño e Innovación, 2015)
The curator of the Salone Satellite di Milano is convinced that young Chilean designers still have much to contribute in the creation of objects using the red metal.